2022
DOI: 10.2147/jhl.s365129
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Organizational Justice and Counter-Productive Work Behavior Among Health Care Professionals in Jimma Zone Public Health Institutions

Abstract: Background Counterproductive behavior costs organizations and their members which will ultimately affect work-related outcomes and organizational success. Organizational justice has the potential to affect the level of counter productive behavior. However, there is a paucity of studies to show the link between counterproductive behavior and organizational justice dimensions in the Ethiopian health care system context. Therefore, the purpose of this research was to look into the link between organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A contingency approach initiates a relationship between perceived supervisor support and job performance. Robbins et al (2013) and Adugna et al (2022) further supported the statement that immediate supervisor support is essential for a non-counterproductive environment. These non-counterproductive environments enhance the self-efficacy of the employees, which can further foster the upward performance cycle of employees in organizations.…”
Section: H4 Work Engagement Improves Job Performancementioning
confidence: 92%
“…A contingency approach initiates a relationship between perceived supervisor support and job performance. Robbins et al (2013) and Adugna et al (2022) further supported the statement that immediate supervisor support is essential for a non-counterproductive environment. These non-counterproductive environments enhance the self-efficacy of the employees, which can further foster the upward performance cycle of employees in organizations.…”
Section: H4 Work Engagement Improves Job Performancementioning
confidence: 92%
“…For example, it could be assumed that with low levels of justice and low levels of health, there is an increased tendency toward counterproductive work behavior (CWB). Thus far, it has been established that, in contrast to distributive justice, procedural and interpersonal justice are positively and significantly associated with CWB [64]. Organizational constraints, interpersonal conflicts and perceived injustice are stressors at work and CWB can be seen as a response to experienced tension [65].…”
Section: Limitations Of the Study And Implications For The Futurementioning
confidence: 99%
“… Predictor. Organizational justice can reduce counterproductive behaviors [ 29 ] and the prevalence of WSH by discouraging perpetrators [ 30 ]. Similarly, Rubino et al [ 31 ] found that sexual harassment is less frequent and, when it occurs, has a lesser impact when greater organizational justice is perceived.…”
Section: Proposed Modelmentioning
confidence: 99%